Computer simulation of gymnastics vault landings - Mills, C. (Loughborough University, 2005)
A computer simulation model of an International Gymnastics Federation (F.I.G.) landing mat and a gymnast was developed to investigate the mechanics of landing from the gymnastics vault. The landing mat model incorporated the multilayer design of the landing mat and its deformation characteristics were based upon experimental data. The gymnast model was based upon an elite level gymnast and contained subject-specific parameters. The gymnast was modelled as a seven-segment link system with 'lumped' muscles producing joint rotation at the hip, knee and ankle. Wobbling masses were included within the trunk, thigh and shank segments to represent soft tissue movement. A two segment bone within the shank and thigh provided estimates of bone bending moments and bone deformations. Joint torques were based upon the torque / angle / angular velocity relationship established during isokinetic dynamometry testing of the subject. The muscle forces were calculated from the joint torques and from moment arm data taken from the literature and scaled to the subject. The gymnast-mat model was evaluated using the kinetic, kinematic and EMG data collected from actual vaults performed by the subject. Evaluation results showed good agreement between the simulations and the actual performances with difference scores between 10.1 % and 23.6 %. The landing strategy and landing mat were optimised to minimise the ground reaction forces and bone bending moments. Optimised landing strategy results suggest that modifications to the gymnast's landing strategy could reduce the peak ground reaction forces but this may not decrease the peak internal joint forces. Optimised landing mat parameter results suggest that a landing mat with 20 % more damping could reduce the peak ground reaction forces and internal joint forces but this may increase the initial impact force between the foot and the mat's surface.